2009
DOI: 10.1086/598938
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Postoperative Gram‐Negative Bacterial Endophthalmitis Associated with Contaminated Trypan Blue Ophthalmic Solution

Abstract: We report 6 cases of postsurgical endophthalmitis due to gram-negative bacteria associated with contaminated trypan blue dye from a compounding pharmacy. Unopened trypan blue syringes yielded Pseudomonas aeruginosa and Burkholderia cepacia complex on culture, with pulsed-field gel electrophoresis patterns indistinguishable from patient isolates. Contamination of compounded medications should be considered when investigating outbreaks of postoperative endophthalmitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 4 publications
1
47
0
2
Order By: Relevance
“…6,9,14,26,29 A last recorded visual acuity of 20/400 or better was noted in 127 of the 229 patients (55.5%), of between 20/400 and light perception in 59 patients (25.8%), and of no light perception in 34 patients (14.8%).…”
Section: Literature Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…6,9,14,26,29 A last recorded visual acuity of 20/400 or better was noted in 127 of the 229 patients (55.5%), of between 20/400 and light perception in 59 patients (25.8%), and of no light perception in 34 patients (14.8%).…”
Section: Literature Analysismentioning
confidence: 94%
“…One study included a patient who developed chronic postoperative (O6 weeks after cataract surgery) endophthalmitis. 9 The possible source of outbreaks included intraoperative solutions, 10 (37%) (5 Z irrigating solution, 2 Z trypan blue, 1 Z reconstituted cefuroxime, 1 Z povidone-iodine, 1 Z hyaluronic acid); phaco machines, 6 (22.2%); ventilation systems, 3 (11.1%); sterilization, 3 (11.1%); and miscellaneous, 3 (1 Z construction dust, 1 Z cotton swab, and 1 Z defective surgical blade); in 5 outbreaks (18.5%), no possible source could be identified. Two reports were identified with more than 2 possible sources of contamination.…”
Section: Literature Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…10,12,17,20 Serratia marcescens is well recognized as a nosocomial pathogen and has been responsible for outbreaks in neonatal and pediatric intensive care units 21 and outbreaks of bloodstream infection associated with intravenous drug solutions. 15 Moreover, respiratory colonization with S. marcescens has been a risk factor for outbreaks of bloodstream infection. 18 Drug-resistant S. marcescens isolates have been emerging in medical settings; these isolates produce aminoglycoside modification enzymes [AAC(6¢)-Ib, AAC(6¢)-Ib-cr, AAC(6¢)-Ic, AAC(6¢)-Iid, and ANT(3")-Ii], 3,4,13,19 16S rRNA methylases (ArmA and RmtB), 1,2 and metallo-blactamases, 9,11,23 although S. marcescens is naturally resistant to tetracycline, amoxicillin, amoxicillin-clavulanate, cephalothin, and colistin.…”
Section: Introductionmentioning
confidence: 99%
“…The concerns over compounding were recently brought to light by Goldberg et al who reported twelve cases of Streptococcus mitis/oralis endophthalmitis caused by contaminated intravitreal bevacizumab prepared by a single compounding pharmacy in South Florida. 18 Centers for Disease Control and Prevention reported a series of 6 post-cataract surgery endophthalmitis cases due to gram-negative bacteria associated with contaminated trypan blue dye from a compounding pharmacy. Unopened trypan blue syringes yielded Pseudomonas aeruginosa and Burkholderia cepacia complex on culture.…”
Section: Introductionmentioning
confidence: 99%